Religião, política e eleições na Folha Universal - Rothberg, Danilo [UNESP]; Dias, Mariane Bovoloni [UNESP] (My University, 2012)
The Folha Universal, newspaper produced by the Igreja Universal do Reino de Deus (Iurd, abbreviation in Portuguese for Universal Church of the Kingdom of God), reaches an average weekly circulation from 2.5 to 3.5 million copies. Studies indicate that the Folha Universal is not merely an institutional newspaper. It is systematically dedicated to be a source of political information to their readers, in order to publicize candidates and politicians who defend the Iurd’s proposals for the Brazilian public life. This paper describes results of an empirical study on the frames built by the Folha Universal about the social demands, economic and political governance considered as priorities to the public management by the Iurd around five themes of analysis: public safety; children and adolescents care; public health; environment; politics and economy. The results indicate that, as characteristics of the Folha Universal in the four months prior to the 2010 Brazilian elections, aspects that differ from those indicated by previous studies on the newspaper. Previously detected in the pages of Folha Universal as a mean for finding solutions to social problems, the theology of prosperity was in our sample replaced by the formulation of public policies.

La Folha Universal de la Iglesia Universal del Reino de Dios (Iurd) llega a los promedios semanales entre 2,5 y 3,5 millones de copias. Estudios indican que la Folha Universal no es sólo un periódico dedicado a la sistematización institucional. Él se dedica a afirmarse como una fuente de información política a sus lectores, con el fin de proyectar los candidatos y los agentes que apoyan las propuestas de la Iurd para la vida pública brasileña. Este artículo describe los resultados del estudio empírico sobre los marcos construidos por Folha Universal acerca de las demandas sociales, económicas y políticas de gobierno consideradas como prioritarias por la Iurd en torno a cinco temáticas de análisis: seguridad pública; infancia y la adolescencia; salud; medio ambiente; política y la economía. Los resultados indican, como las características do periódico, en los cuatro meses anteriores a las elecciones de 2010, aspectos que difieren de los indicados por estudios anteriores. Antes manifesta en las páginas de la Folha Universal como un medio para encontrar soluciones a los problemas sociales, la teología de la prosperidad en la muestra fue sustituida por la formulación de políticas públicas.

A Folha Universal, jornal da Igreja Universal do Reino de Deus (Iurd), atinge tiragens semanais médias entre 2,5 e 3,5 milhões de exemplares. Estudos indicam que a Folha Universal não é meramente um jornal institucional. Ele se dedica com sistematização a se afirmar como fonte de informação política aos seus leitores, de maneira a projetar candidatos e mandatários que defendem as propostas da Iurd para a vida pública brasi-leira. Este artigo descreve resultados de estudo empírico sobre os enquadramentos construídos pela Folha Universal a respeito das demandas sociais, econômicas e políticas consideradas prioritárias à gestão pública pela Iurd em torno de cinco temáticas de análise: segurança pública; infância e adolescência; saúde; meio ambiente; política e economia. Os resultados indicam, como características da Folha Universal nos quatro meses anteriores às eleições de 2010, aspectos que se diferenciam daqueles apontados por estudos anteriores sobre o jornal. Antes presente nas páginas da Folha Universal como meio de busca por soluções para problemas sociais, a teologia da prosperidade foi substituída na amostra analisada pela formu-lação de políticas públicas.
Religion, politics and elections in the Folha Universal
Religión, política y elecciones en la Folha Universal
Keywords: Evangelical faith; Communication; Politics; Elections; Fe evangélica; Comunicación; Política; Elecciones; Fé evangélica; Comunicação; Política; Eleições